A MDE-Based Approach for Developing Multi-Agent Systems - Silva, Viviane; de Maria, Beatriz; de Lucena, Carlos (Electronic Communications of the EASST, 2007)
This paper focuses on the development of multi-agent systems based on a model driven engineering approach. Our goal is to cope with the traceability between design and implementation models and with the always changing characteristics of such systems.